Coil component, circuit board, electronic device, and method for manufacturing coil component
The magnetic substrate design with varying metal magnetic particles and a directional magnetic gap portion addresses magnetic saturation and flux concentration, enhancing DC superimposition characteristics and inductance.
Patent Information
- Application Number
- JP2021030452
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-26
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-02-26
AI Technical Summary
Conventional magnetic substrates with metal magnetic particles of different relative magnetic permeabilities experience magnetic saturation issues and reduced inductance due to high molding pressures, leading to poor DC superimposition characteristics.
A magnetic substrate design with first and second metal magnetic particles of varying elastic limits and permeabilities, incorporating a magnetic gap portion that covers the surface of the first particles, with a thickness in the coil axis direction greater than in the perpendicular direction, formed by gaps or resin, to manage magnetic flux distribution.
The design achieves both high magnetic permeability and improved DC superimposition characteristics by preventing flux concentration and reducing magnetic saturation, while maintaining inductance.
Smart Images

Figure 0007605656000002 
Figure 0007605656000003 
Figure 0007605656000004
Abstract
Description
[Technical field]
[0001] The disclosure of this specification relates to a coil component, a circuit board, an electronic device, and a method for manufacturing a coil component. [Background technology]
[0002] Conventionally, coil components having a magnetic base containing multiple kinds of metal magnetic particles have been known. For example, Japanese Patent Application Laid-Open No. 63-271905 describes that a magnetic base having high magnetic permeability and excellent DC bias characteristics can be manufactured by pressure molding a mixture of metal magnetic particles made of a hard Fe-Si-Al alloy and pure iron powder, which is softer than the Fe-Si-Al alloy. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 63-271905 Summary of the Invention [Problem to be solved by the invention]
[0004] Conventionally, when a magnetic base for a coil component is produced by pressure molding, a high molding pressure is used to increase the packing density of the metal magnetic particles and realize high magnetic permeability. For example, in Patent Document 1, a pressure of 20 ton / cm is used. 2 A molding pressure of 10 ...
[0005] In this way, in a conventional magnetic base containing metal magnetic particles made of two or more types of magnetic materials with different relative magnetic permeabilities, there are magnetic paths where magnetic saturation is likely to occur and magnetic paths where it is unlikely to occur. Therefore, when the DC current flowing through the coil conductor increases, magnetic saturation occurs in stages, starting with the magnetic paths that are more likely to cause magnetic saturation, and the inductance of the coil component gradually decreases. For this reason, it is difficult to achieve high DC superposition characteristics in a magnetic base containing metal magnetic particles made of two or more types of magnetic materials with different relative magnetic permeabilities and molded at a high molding pressure.
[0006] On the other hand, if the molding pressure is low, the filling rate of the metal magnetic particles in the magnetic base will be low, making it difficult to achieve high inductance.
[0007] An object of the present invention is to solve or alleviate at least some of the above-mentioned problems. More specifically, one of the objects of the present invention is to improve the DC bias characteristics of a coil component having a magnetic base containing metal magnetic particles made of two or more types of magnetic materials having mutually different relative magnetic permeabilities.
[0008] A more specific object of the present invention is to achieve both high magnetic permeability and high DC bias characteristics in a coil component having a magnetic base containing metal magnetic particles made of two or more types of magnetic materials having mutually different relative magnetic permeabilities.
[0009] Objects of the invention disclosed in this specification other than those mentioned above will become apparent by referring to the entire specification. The invention disclosed in this specification may solve the problems understood from the description of this specification instead of or in addition to the above problems. [Means for solving the problem]
[0010] A coil component according to an embodiment of the present invention includes a coil conductor extending around a coil axis and a magnetic base arranged to include the coil axis, the magnetic base having first metal magnetic particles having a first elastic limit and a first relative magnetic permeability, second metal magnetic particles having a second elastic limit smaller than the first elastic limit and a second relative magnetic permeability lower than the first relative magnetic permeability, and a magnetic gap portion covering a surface of the first metal magnetic particles and configured such that a first thickness in a first direction along the coil axis is greater than a second thickness in a second direction perpendicular to the first direction.
[0011] In one aspect of the present invention, the magnetic gap portion includes a first magnetic gap element that is composed of at least one of an air gap and a resin and covers one end of the first metal magnetic particle in the first direction.
[0012] In one embodiment of the present invention, the first magnetic gap element extends circumferentially around the first metal magnetic particle over a length that is greater than or equal to 1 / 16 and less than 1 / 2 of the circumference of the first metal magnetic particle when observed in a cross section of the magnetic base cut on a plane passing through the coil axis.
[0013] In one embodiment of the present invention, the magnetic gap portion has a second magnetic gap element including an oxide of an element contained in the first metal magnetic particle.
[0014] In one aspect of the present invention, a thickness of the second magnetic gap element in the first direction is greater than a thickness of the second magnetic gap element in the second direction.
[0015] In one embodiment of the present invention, when observed in a cross section of the magnetic base cut on a plane passing through the coil axis, the dimension of the magnetic gap portion in the first direction is 0.5% or more and 4.0% or less of the dimension of the first metal magnetic particle in the first direction.
[0016] In one embodiment of the present invention, the first metal magnetic particles and the second metal magnetic particles are both composed of an Fe-Si alloy, and the Si content in the first metal magnetic particles is greater than the Si content in the second metal magnetic particles.
[0017] In one embodiment of the present invention, the first metal magnetic particles have a lower Fe content than the second metal magnetic particles.
[0018] In the magnetic base according to one embodiment of the present invention, the volume ratio of the first metal magnetic particles to the total volume of the first metal magnetic particles and the second metal magnetic particles is in the range of 10 to 65 vol %.
[0019] In one aspect of the present invention, the magnetic base is formed by pressing an element including the first metal magnetic particles and the second metal magnetic particles in the first direction.
[0020] In one aspect of the present invention, the magnetic gap portion includes another first magnetic gap element that is composed of at least one of an air gap and a resin and covers the other end of the first metal magnetic particle in the first direction.
[0021] A circuit board according to an aspect of the present invention includes any one of the coil components described above.
[0022] An electronic device according to an aspect of the present invention includes the above-mentioned circuit board.
[0023] One aspect of the present invention relates to a method for manufacturing a coil component, the method comprising the steps of filling a magnetic material including first metal magnetic particles having a first relative magnetic permeability and second metal magnetic particles having a second relative magnetic permeability lower than the first relative magnetic permeability into a die cavity in which a coil conductor extending around a coil axis is disposed, pressurizing the magnetic material in a direction along the coil axis with a molding pressure smaller than the elastic limit of the first metal magnetic particles and larger than the elastic limit of the second metal magnetic particles to form a green body, and heat-treating the green body after removing the molding pressure to form a magnetic base.
[0024] A manufacturing method according to one embodiment of the present invention includes the steps of: preparing a plurality of magnetic sheets from a mixed magnetic material containing first metal magnetic particles having a first relative magnetic permeability and second metal magnetic particles having a second relative magnetic permeability lower than the first relative magnetic permeability; forming a conductive pattern on the surface of each of the plurality of magnetic sheets; stacking the plurality of magnetic sheets with the conductive patterns formed thereon in a stacking direction to form a laminate; forming a molded body by pressing the laminate in the stacking direction with a pressure smaller than the elastic limit of the first metal magnetic particles and greater than the elastic limit of the second metal magnetic particles; and heat-treating the molded body after removing the molding pressure to form a magnetic base.
[0025] A manufacturing method according to one embodiment of the present invention includes a step of applying a molding pressure in one axial direction to a mixed magnetic material including first metal magnetic particles having a first relative magnetic permeability and second metal magnetic particles having a second relative magnetic permeability lower than the first relative magnetic permeability, the molding pressure being smaller than the elastic limit of the first metal magnetic particles and larger than the elastic limit of the second metal magnetic particles, to form a molded body; a step of heat-treating the molded body to form a magnetic base; and a step of providing a coil conductor on the magnetic base so as to extend around the uniaxial direction. Effect of the Invention
[0026] According to at least one embodiment of the present invention, it is possible to improve the DC bias characteristics in a coil component having a magnetic base including metal magnetic particles made of two or more types of magnetic materials each having a different relative magnetic permeability. [Brief description of the drawings]
[0027] [Figure 1] FIG. 1 is a perspective view showing a coil component according to an embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view that illustrates a schematic cross section of the coil component of FIG. 1 taken along line II. [Diagram 3] 3 is an enlarged schematic view of a region A of the magnetic substrate in FIG. 2. FIG. [Figure 4] 4 is an enlarged view of a region B of the magnetic base in FIG. 3, showing a magnetic gap portion 40 according to an embodiment of the present invention. [Diagram 5] FIG. 4 is a flow chart showing the flow of a manufacturing method of a coil component according to an embodiment of the present invention. [Figure 6] 4A to 4C are schematic diagrams illustrating elastic deformation of first metal magnetic particles in a compression molding process. [Figure 7] 4 is an enlarged view of a region B of the magnetic base in FIG. 3, showing a magnetic gap portion 40 according to another embodiment of the present invention. [Figure 8] FIG. 11 is an exploded perspective view showing a coil component according to another embodiment of the present invention. [Figure 9] FIG. 11 is a front view illustrating a coil component according to still another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Various embodiments of the present invention will be described below with reference to the drawings as appropriate. Note that components common to multiple drawings are given the same reference numerals throughout the multiple drawings. Please note that the drawings are not necessarily drawn to scale for the sake of convenience. The embodiments of the present invention described below do not limit the invention according to the claims. Elements described in the following embodiments are not necessarily essential to the solution of the invention.
[0029] A coil component 1 according to an embodiment of the present invention will be described with reference to Figs. 1 and 2. Fig. 1 is a perspective view showing the coil component 1, and Fig. 2 is a schematic cross-sectional view showing the cross section of the coil component 1 cut along line II in Fig. 1. As shown in the figure, the coil component 1 includes a base 10, a coil conductor 25 provided on the base 10, an external electrode 21 provided on the surface of the base 10, and an external electrode 22 provided on the surface of the base 10 at a position spaced apart from the external electrode 21. The base 10 includes a magnetic material. For this reason, in this specification, the base 10 may be referred to as a magnetic base 10. In Fig. 1, the coil conductor 25 provided inside the magnetic base 10 is illustrated by projecting the magnetic base 10.
[0030] In this specification, the arrangement, dimensions, shape, and other aspects of each member may be described based on the "L axis," "W axis," and "T axis" shown in Figures 1 and 2. In this specification, the "length" direction, "width" direction, and "thickness" direction of coil component 1 may be respectively referred to as the "L axis" direction, the "W axis" direction, and the "T axis" direction in Figure 1. The "thickness" direction may also be referred to as the "height" direction.
[0031] The coil component 1 can be mounted on a mounting board 2a. The mounting board 2a is provided with land portions 3a and 3b. The coil component 1 is mounted on the mounting board 2a by joining an external electrode 21 to the land portion 3a and connecting an external electrode 22 to the land portion 3b. A circuit board 2 according to an embodiment of the present invention includes the coil component 1 and a mounting board 2a on which the coil component 1 is mounted. The circuit board 2 can be mounted on various electronic devices. Electronic devices on which the circuit board 2 can be mounted include smartphones, tablets, game consoles, automotive electrical equipment, servers, and various other electronic devices.
[0032] The coil component 1 may be an inductor, a transformer, a filter, a reactor, or any other of various coil components. The coil component 1 may be a coupled inductor, a choke coil, or any other of various magnetically coupled coil components. The coil component 1 may be, for example, a power inductor used in a DC / DC converter. The applications of the coil component 1 are not limited to those explicitly stated in this specification.
[0033] The magnetic base 10 is made of a magnetic material and has a roughly rectangular parallelepiped shape. In one embodiment of the present invention, the magnetic base 10 is formed so that the length dimension (dimension in the L-axis direction) is 1.0 mm to 6.0 mm, the width dimension (dimension in the W-axis direction) is 1.0 mm to 6.0 mm, and the height dimension (dimension in the T-axis direction) is 1.0 mm to 5.0 mm. The dimensions of the magnetic base 10 are not limited to the dimensions specifically described in this specification. In this specification, the term "rectangular parallelepiped" or "rectangular parallelepiped shape" does not only mean "rectangular parallelepiped" in the mathematically strict sense. The dimensions and shape of the magnetic base 10 are not limited to those explicitly described in this specification.
[0034] The magnetic base 10 has a first main surface 10a, a second main surface 10b, a first end surface 10c, a second end surface 10d, a first side surface 10e, and a second side surface 10f. The outer surface of the magnetic base 10 is defined by these six surfaces. The first main surface 10a and the second main surface 10b form the surfaces at both ends of the magnetic base 10 in the height direction, the first end surface 10c and the second end surface 10d form the surfaces at both ends of the magnetic base 10 in the length direction, and the first side surface 10e and the second side surface 10f form the surfaces at both ends of the magnetic base 10 in the width direction.
[0035] As shown in Fig. 1, the first main surface 10a is located on the upper side of the magnetic base 10, and therefore the first main surface 10a is sometimes referred to as the "upper surface". Similarly, the second main surface 10b is sometimes referred to as the "lower surface". The coil component 1 is disposed so that the second main surface 10b faces the substrate 2, and therefore the second main surface 10b is sometimes referred to as the "mounting surface". When referring to the up-down direction of the coil component 1, the up-down direction in Fig. 1 is used as the reference.
[0036] In one embodiment of the present invention, the external electrode 21 is provided on the mounting surface 10b and the end surface 10c of the magnetic base 10. The external electrode 22 is provided on the mounting surface 10b and the end surface 10d of the magnetic base 10. The shapes and arrangements of the external electrodes 21, 22 are not limited to the example shown in the figure. The external electrodes 21 and 22 are arranged spaced apart from each other in the length direction.
[0037] The coil conductor 25 is wound in a spiral shape around a coil axis Ax extending along the thickness direction (T-axis direction). One end of the coil conductor 25 is connected to the external electrode 21, and the other end is connected to the external electrode 22. In the illustrated embodiment, only both ends of the coil conductor 25 are exposed from the magnetic base 10, and the other portions are provided inside the magnetic base 10. In this manner, at least a portion of the coil conductor 25 is covered by the magnetic base 10. In the illustrated embodiment, the coil axis Ax intersects with the first main surface 10a and the second main surface 10b, but does not intersect with the first end surface 10c, the second end surface 10d, the first side surface 10e, and the second side surface 10f. In other words, the first end surface 10c, the second end surface 10d, the first side surface 10e, and the second side surface 10f extend along the coil axis Ax. The cross section of FIG. 2 shows a cross section of the magnetic base 10 cut along a plane passing through this coil axis Ax.
[0038] In one embodiment of the present invention, the magnetic substrate 10 is made of a magnetic material containing a plurality of types of metal magnetic particles. The microscopic structure of the magnetic substrate 10 will be described with reference to Figs. 3 and 4. Fig. 3 is a schematic enlarged view of a region A shown in Fig. 2 in the cross section of the magnetic substrate 10, and Fig. 4 is a schematic enlarged view of a region B shown in Fig. 3 in the cross section of the magnetic substrate 10. As shown in Fig. 3, the magnetic substrate 10 in one embodiment includes a plurality of first metal magnetic particles 31 and a plurality of second metal magnetic particles 32. Since the cross section of the magnetic substrate 10 includes a large number of first metal magnetic particles 31 and second metal magnetic particles 32, only a portion of the first metal magnetic particles 31 and second metal magnetic particles 32 shown in Figs. 3 and 4 are labeled. An insulating film may be provided on the surface of the first metal magnetic particles 31 and the second metal magnetic particles 32. In this case, adjacent metal magnetic particles are bonded to each other via the insulating film. In addition, the insulating film electrically insulates adjacent metal magnetic particles from each other. As described later, the insulating film may be an oxide film containing an oxide of a constituent element of the metal magnetic particle. Adjacent ones of the plurality of first metal magnetic particles 31 and the plurality of second metal magnetic particles 32 may be bonded to each other by an insulating binder. In this specification, when it is not necessary to distinguish between the first metal magnetic particles 31 and the second metal magnetic particles 32, the first metal magnetic particles 31 and the second metal magnetic particles 32 may be simply called metal magnetic particles without distinguishing between them.
[0039] The first metal magnetic particles 31 and the second metal magnetic particles 32 are each made of a soft magnetic material. In one embodiment, the first metal magnetic particles 31 and the second metal magnetic particles 32 are each made of a soft magnetic material mainly composed of Fe. Specifically, the first metal magnetic particles 31 and the second metal magnetic particles 32 are each (1) metal particles such as Fe, Ni, etc., (2) crystalline alloy particles such as Fe-Si-Cr alloy, Fe-Si-Al alloy, Fe-Si alloy, Fe-Ni alloy, etc., (3) amorphous alloy particles such as Fe-Si-B alloy, Fe-Si-Cr-BC alloy, Fe-Si-Cr-B alloy, etc., or (4) mixed particles of these. The composition of the metal magnetic particles contained in the magnetic base 10 is not limited to the above.
[0040] The materials of the first metal magnetic particles 31 and the second metal magnetic particles 32 are selected so that the elastic limit of the material of the first metal magnetic particles 31 is greater than the elastic limit of the material of the second metal magnetic particles 32, and the relative magnetic permeability of the material of the first metal magnetic particles 31 is greater than the relative magnetic permeability of the material of the second metal magnetic particles 32. The "elastic limit" of a metal magnetic particle means the limit value of stress at which the metal magnetic particle returns to its original shape when the load is removed, even if the metal magnetic particle is deformed by applying a load. In accordance with the usual usage by those skilled in the art, a deformation in which the permanent distortion remaining in the dimensions after the load is removed is within 0.02% of the dimensions before the load is applied is determined to be a deformation within the elastic limit.
[0041] The material of the first metal magnetic particles 31 can be an Fe-based amorphous alloy. Amorphous has a high elastic limit because the atomic structure is random. As described above, amorphous alloys that can be used as the material of the first metal magnetic particles 31 include Fe-Si-B amorphous alloy, Fe-Si-Cr-BC amorphous alloy, and Fe-Si-Cr-B amorphous alloy. The material of the second metal magnetic particles 32 can include pure metal particles. When the above-mentioned amorphous alloy is used as the material of the first metal magnetic particles 31, for example, carbonyl iron or pure Ni can be used as the material of the second metal magnetic particles 32. Carbonyl iron and pure Ni are soft and have a lower elastic limit than Fe-based amorphous alloy particles. In particular, the above-mentioned Fe-Si-B amorphous alloy, Fe-Si-Cr-BC amorphous alloy, and Fe-Si-Cr-B amorphous alloy all have a higher relative permeability than carbonyl iron and pure Ni.
[0042] The material of the first metal magnetic particle 31 and the second metal magnetic particle 32 may be an alloy containing the same type of metal element at different content ratios. For example, both the first metal magnetic particle 31 and the second metal magnetic particle 32 may be particles of an Fe-Si alloy. In this case, by making the content ratio of Si higher than the content ratio of Si in the second metal magnetic particle 32, the elastic limit of the first metal magnetic particle 31 can be made higher than the elastic limit of the second metal magnetic particle 32, and the relative permeability of the material of the first metal magnetic particle 31 can be made higher than the relative permeability of the material of the second metal magnetic particle 32. In one embodiment, both the first metal magnetic particle 31 and the second metal magnetic particle 32 may be particles of an Fe-Si-Cr alloy. In one embodiment, both the first metal magnetic particle 31 and the second metal magnetic particle 32 may be particles of an Fe-Si-Al alloy. Even in these cases, by making the Si content in the first metal magnetic particles 31 higher than the Si content in the second metal magnetic particles 32, the elastic limit of the first metal magnetic particles 31 can be made higher than the elastic limit of the second metal magnetic particles 32, and the relative permeability of the material of the first metal magnetic particles 31 can be made higher than the relative permeability of the material of the second metal magnetic particles 32.
[0043] In this way, the first metal magnetic particles 31 and the second metal magnetic particles 32 contain different types of elements, or even if they are made of the same type of elements, their compositions are different, so the first metal magnetic particles 31 and the second metal magnetic particles 32 can be distinguished by performing energy dispersive X-ray spectroscopy (EDS) on an SEM image of a cross section of the magnetic substrate 10. For example, the composition of each particle can be analyzed by EDS, and particles with a molar ratio of iron lower than a predetermined value can be determined as the first metal magnetic particles 31. The composition of each particle can also be analyzed by EDS, and particles with a molar ratio of Si higher than a predetermined value can be determined as the first metal magnetic particles 31.
[0044] In one embodiment, the average particle size of the second metal magnetic particles 32 may be smaller than the average particle size of the plurality of first metal magnetic particles 31 contained in the magnetic base 10. For example, the average particle size of the second metal magnetic particles 32 may be 1 / 2 or less, 1 / 3 or less, 1 / 4 or less, 1 / 5 or less, 20 / 3 or less, or 1 / 10 or less of the average particle size of the first metal magnetic particles 31. The average particle sizes of the first metal magnetic particles 31 and the second metal magnetic particles 32 are determined based on the particle size distribution obtained by cutting the magnetic base 10 along its thickness direction (T-axis direction) to expose the cross section, and obtaining a particle size distribution based on an SEM image of the cross section taken by a scanning electron microscope (SEM). For example, the 50% value (D50) of the particle size distribution obtained based on the SEM image can be the average particle size of the metal magnetic particles. The average particle size of the first metal magnetic particles 31 can be, for example, in the range of 1 μm to 50 μm, and the average particle size of the second metal magnetic particles 32 can be, for example, in the range of 0.1 μm to 20 μm. When the average particle size of the second metal magnetic particles 32 is smaller than the average particle size of the first metal magnetic particles 31, the second metal magnetic particles 32 tend to penetrate between two adjacent first metal magnetic particles 31, and as a result, the filling rate (density) of the metal magnetic particles in the magnetic base 10 can be increased.
[0045] In one embodiment of the present invention, the volume ratio of the total volume of the first magnetic particles 31 to the total volume of the first metal magnetic particles 31 and the second metal magnetic particles 32 may be 10 to 65 vol %.
[0046] The metal magnetic particles contained in the magnetic base 10 are not limited to the first metal magnetic particles 31 and the second metal magnetic particles 32. The magnetic base 10 may include third metal magnetic particles having a lower elastic limit than the first metal magnetic particles 31 and a different elastic limit and relative magnetic permeability than both the first metal magnetic particles 31 and the second metal magnetic particles 32.
[0047] The magnetic substrate 10 can be produced by kneading mixed particles including a plurality of first metal magnetic particles 31 and a plurality of second metal magnetic particles 32 with a resin and a dilution solvent to produce a mixed resin composition, placing the mixed resin composition in the molding die under molding pressure to produce a molded body, and subjecting the molded body to a heat treatment. The molding pressure is applied in the direction of the coil axis Ax of the coil conductor 25 (in the illustrated embodiment, the T-axis direction). For example, the coil conductor 25 is placed in the molding die so that the coil axis Ax of the coil conductor 25 is parallel to the pressure direction, and insert molding is performed, whereby molding pressure can be applied in the direction of the coil axis Ax of the coil conductor 25.
[0048] The resin in the mixed resin composition may be a thermosetting resin. The resin may be cured by a heat treatment process to become a binder that binds adjacent particles of the first metal magnetic particles 31 and the second metal magnetic particles 32. In this case, at least a part of the gap between the first metal magnetic particles 31 and the second metal magnetic particles 32 of the magnetic base 10 is filled with the cured resin. The resin in the mixed resin composition may be thermally decomposed in the heat treatment process. In this case, the finished magnetic base 10 may not contain the resin in the resin composition.
[0049] A magnetic gap portion 40 made of a low magnetic permeability material having a relative magnetic permeability lower than that of the material of the first metal magnetic particle 31 is provided around the first metal magnetic particle 31. By providing the magnetic gap portion 40 around the first metal magnetic particle 31, the distance between the first metal magnetic particle 31 and the metal magnetic particle (the first metal magnetic particle 31 and / or the second metal magnetic particle 32) adjacent to the first metal magnetic particle 31 becomes larger than when the magnetic gap portion 40 is not provided. In other words, the magnetic gap portion 40 is interposed between the first metal magnetic particle 31 and the metal magnetic particle adjacent to the first metal magnetic particle 31. The magnetic gap portion 40 is provided so as to cover the surface of the first metal magnetic particle 31. The magnetic gap portion 40 can include a first magnetic gap element provided at least one end of the first metal magnetic particle 31 in the T-axis direction (i.e., the pressure direction) and a second magnetic gap element covering the entire surface of the first metal magnetic particle 31. The second magnetic gap element covering the surface of the first metal magnetic particle 31 may be provided radially inward of the first metal magnetic particle 31 relative to the first magnetic gap element. The second metal magnetic particle 32 may be in direct contact with the surface of the first metal magnetic particle 31. The first magnetic gap element may be in direct contact with the first metal magnetic particle 31 when the second gap element is not provided. In the illustrated embodiment, an insulating film 41 is provided as the second magnetic gap element on the entire surface of the first metal magnetic particle 31, and the first magnetic gap element 40a is provided at the positive end of the first metal magnetic particle 31 in the T-axis direction (i.e., the pressure direction) through this insulating film 41, and the magnetic gap element 40b is provided at the negative end. In this way, the first magnetic gap element provided in one first metal magnetic particle 31 may be divided into the first magnetic gap element 40a at one end in the T-axis direction and the first magnetic gap element 40b at the other end. In the same sense as in the partial omission of the reference numeral "31," in Figs. 3 and 4, reference numerals are attached to only some of the first magnetic gap elements 40a, 40b.
[0050] The first magnetic gap elements 40a and 40b may be an air gap or a resin. The first magnetic gap elements 40a and 40b may be partly an air gap and partly a resin. In this case, the air gap and the resin are combined to form the first magnetic gap element 40a or the first magnetic gap element 40b.
[0051] As described above, in the illustrated embodiment, the second magnetic gap element is an insulating film 41 covering the entire surface of the first metal magnetic particle 31. The insulating film 41 may be an oxide film made of an oxide of an element (e.g., F, Cr, Si, Cr, Al) contained in the first metal magnetic particle 31. The oxide of an element contained in the first metal magnetic particle 31 has a smaller relative permeability than the element itself. The insulating film containing the oxide of an element contained in the first metal magnetic particle 31 may be formed on the surface of the first metal magnetic particle 31 during heat treatment in the manufacturing process of the coil component 1. The insulating film 41 contained in the metal magnetic particle may be a coating film made of an insulating material. This coating film may be a thin film containing silicon oxide formed on the surface of the first metal magnetic particle 31 by a coating process using, for example, a sol-gel method. To form a coating film made of silicon oxide on the surface of the metal magnetic particles by the sol-gel method, first, a mixture containing the metal magnetic particles, ethanol, and ammonia water is mixed with a treatment liquid containing TEOS (tetraethoxysilane, Si(OC2H5)4), ethanol, and water to prepare a mixture, then the mixture is stirred, and the stirred mixture is then filtered. This allows the metal magnetic particles with the silicon oxide film on each surface to be separated from the mixture.
[0052] The magnetic gap section 40 may or may not include a second magnetic gap element. For example, when the metal magnetic particles are bonded to each other via an insulating binder made of a thermosetting resin, the insulating film 41 is not essential on the surface of the first metal magnetic particle 31. In this case, the magnetic gap section 40 may not include a second magnetic gap element.
[0053] The magnetic gap portion 40 may be made of a low magnetic permeability material other than those mentioned above, which has a lower relative magnetic permeability than the material that constitutes the first metal magnetic particles 31.
[0054] In one embodiment of the present invention, the thickness dimensions T21a and T21b of the magnetic gap portion 40 in the T-axis direction are 0.5% to 4.0% of the dimension T11 of the first metal magnetic particle 31 in the T-axis direction. The thickness dimensions T21a and T21b of the magnetic gap portion 40 may each be in the range of 100 nm to 3000 nm. The dimension T21a means the length of a part of a straight line that is parallel to the T-axis and overlaps with the cross section of the first metal magnetic particle 31 and is extended to the positive side of the T-axis direction, and intersects with the magnetic gap portion 40. For example, in the embodiment shown in FIG. 4, the thickness dimension T21a of the magnetic gap portion 40 is the sum of the thickness of the insulating film 41 in the T-axis direction and the thickness of the first magnetic gap element 40a in the T-axis direction. Similarly, the dimension T21b means the length of a part of a straight line that is extended to the negative side of the T-axis direction and intersects with the magnetic gap portion 40. For example, in the embodiment shown in Fig. 4, the thickness dimension T21b of the magnetic gap portion 40 is the sum of the thickness of the insulating film 41 in the T-axis direction and the thickness of the first magnetic gap element 40b in the T-axis direction. The magnetic base 10 includes a plurality of first metal magnetic particles 31, and considering that the dimensions 21a and 21b of the magnetic gap portion 40 provided at the end of the first metal magnetic particle 31 in the T-axis direction may vary for each first metal magnetic particle 31, the dimensions 21a and 21b of the magnetic gap portion 40 are defined as follows in this specification. First, the magnetic base 10 is cut along the T-axis direction to expose the cross section, and an SEM image of the cross section taken at a predetermined magnification by a scanning electron microscope (SEM) is subjected to EDS analysis to analyze the composition of each particle included in the SEM image, and 20 particles with the lowest molar ratio of iron among all particles included in the SEM image are set as the first metal magnetic particles 31 to be measured. The measurement magnification can be determined so that the vertical and horizontal dimensions of the observation field are 3 to 10 times the diameter of the largest first metal magnetic particle 31 contained in the SEM image.Then, for each of the 20 first metal magnetic particles 31 to be measured, the dimension T21a and the dimension T21b defined as above are measured, and the average value of the dimension T21a measured for the 20 first metal magnetic particles 31 to be measured is set as the dimension T21a in the T-axis direction of the magnetic gap portion 40 for the magnetic base 10, and the average value of the dimension T21b measured for the 20 first metal magnetic particles 31 is set as the dimension T21b in the T-axis direction of the magnetic gap portion 40 for the magnetic base 10. The metal magnetic particles, the insulating film 41, and the first magnetic gap elements 40a and 40b can be distinguished from each other by the difference in brightness in the SEM image. Some of the first metal magnetic particles 31 to be measured may include those in which the magnetic gap portion 40 is not observed at the end in the T-axis direction. The magnetic gap portion 40 may not be formed at the end in the T-axis direction of some of the first metal magnetic particles 31, and even if the magnetic gap portion 40 is formed at the end in the T-axis direction of the first metal magnetic particles 31, the magnetic gap portion 40 may not be observed if the cutting position for exposing the cross section passes through a position away from the center of the first metal magnetic particle 31. For first metal magnetic particles 31 among the measurement targets that do not have a magnetic gap portion 40, the values of T21a and T21b can be set to 0 and used to calculate the average value.
[0055] In one embodiment of the present invention, the magnetic gap portion 40 is configured such that its thickness dimensions T21a and T21b in the T-axis direction are thicker than the thickness dimension of the magnetic gap portion 40 in a direction perpendicular to the T-axis direction. FIG. 4 shows the thickness dimensions T22a and T22b of the magnetic gap portion 40 in the L-axis direction perpendicular to the T-axis direction. The magnetic gap portion 40 is configured such that the thickness dimensions T21a and T21b in the T-axis direction are larger than the thickness dimensions T22a and T22b in the L-axis direction perpendicular to the T-axis direction. Although the dimension of the magnetic gap portion 40 in the W-axis direction is not shown, the W-axis direction is also perpendicular to the T-axis direction, so that the thickness dimension of the magnetic gap portion 40 in the W-axis direction is smaller than the thickness dimensions T21a and T21b in the T-axis direction. The thickness dimensions T22a and T22b of the magnetic gap portion 40 in the L-axis direction are defined and measured in the same manner as the thickness dimensions T21a and T21b in the T-axis direction. As described below, the ends of the first metal magnetic grains 31 in the L-axis direction are not covered by the first magnetic gap elements 40a, 40b, and therefore the thickness dimensions T22a, T22b of the magnetic gap portion 40 in the L-axis direction are equal to the thickness of the insulating film 41 in the L-axis direction. The insulating film 41 may have approximately the same thickness along the entire circumference of the first metal magnetic grains 31. In one embodiment of the present invention, the thickness of the insulating film 41 (equal to the thickness dimensions T22a, T22b of the magnetic gap portion 40 in the L-axis direction) is less than 100 nm.
[0056] Next, the details of the first magnetic gap elements 40a and 40b will be further described with reference to FIG. 4. The first magnetic gap element 40a is provided on the positive side of the first metal magnetic particle 31 in the T-axis direction, and the first magnetic gap element 40b is provided on the negative side of the first metal magnetic particle 31 in the T-axis direction. The first magnetic gap elements 40a and 40b are in contact with the first metal magnetic particle 31 directly or via the insulating film 41, and cover a partial area of the surface of the first metal magnetic particle 31, but do not cover the entire surface of the first metal magnetic particle 31. The first magnetic gap element 40a covers an area of the surface of the first metal magnetic particle 31 that includes the end on the positive side in the T-axis direction, and the first magnetic gap element 40b covers an area of the surface of the first metal magnetic particle 31 that includes the end on the negative side in the T-axis direction. The first magnetic gap elements 40a, 40b extend in the circumferential direction of the first metal magnetic particle 31 over a length of 1 / 16 or more and less than 1 / 2 of the circumferential length of the first metal magnetic particle 31. If the length of the first magnetic gap elements 40a, 40b in the circumferential direction of the first metal magnetic particle 31 is less than 1 / 16 of the circumferential length of the first metal magnetic particle 31, the function as a magnetic gap is poor. On the other hand, if the length of the first magnetic gap elements 40a, 40b is 1 / 2 or more of the circumferential length of the first metal magnetic particle 31, the first metal magnetic particle 31 is surrounded by a magnetic gap, which makes it difficult for magnetic flux to pass through the first metal magnetic particle 31, causing inductance deterioration. Therefore, in order to suppress deterioration of inductance and function as a magnetic gap, the length of the first magnetic gap elements 40a, 40b in the circumferential direction of the first metal magnetic particle 31 is set to 1 / 16 or more and less than 1 / 2 of the circumferential length of the first metal magnetic particle 31.
[0057] Neither of the first magnetic gap elements 40a, 40b is provided at the end in the L-axis direction of the first metal magnetic particle 31. In the illustrated embodiment, both ends in the L-axis direction of the first metal magnetic particle 31 are in contact with the second metal magnetic particle 32 via the insulating film 41. When another first metal magnetic particle 31 is present adjacent to one first metal magnetic particle 31, at least one end of the first metal magnetic particle 31 in the L-axis direction may be in contact with the other first metal magnetic particle 31 via the insulating film 41.
[0058] Since the magnetic base 10 in the embodiment of the present invention has the first magnetic gap elements 40a and 40b, it is possible to achieve both high magnetic permeability and high DC superposition characteristics, as described below. In conventional coil components, metal magnetic particles are densely packed to increase magnetic permeability, so there are no parts in the magnetic base that correspond to the first magnetic gap elements 40a and 40b. In conventional coil components, an insulating film may be provided on the surface of the metal magnetic particles in the magnetic base, but the insulating film is formed on the surface of the metal magnetic particles so as to have a uniform thickness in the circumferential direction of the metal magnetic particles, and the thickness dimension in the coil axis direction (the direction corresponding to the T-axis direction) is not formed to be thicker than the thickness in the direction perpendicular to the coil axis direction. That is, there are no parts in conventional coil components that correspond to the first magnetic gap elements 40a and 40b. When two types of metal magnetic particles made of materials with different relative magnetic permeability are densely packed in a magnetic base, the magnetic flux generated when a current flows through a coil conductor preferentially passes through a magnetic path in which there are many high-permeability particles made of a magnetic material with a high relative magnetic permeability, so that when the direct current flowing through the coil conductor increases, magnetic saturation occurs in the order of magnetic paths in which the high-permeability particles are present among the multiple magnetic paths in the magnetic base through which the magnetic flux passes. In the embodiment of the present invention, the first magnetic gap elements 40a and 40b are provided at at least one end in the T-axis direction of the first metal magnetic particles 31 having a higher relative magnetic permeability than the second metal magnetic particles 32, so that magnetic saturation in the magnetic path in which there are many high-permeability particles can be suppressed. In addition, the first magnetic gap elements 40a and 40b are provided at the end in the T-axis direction parallel to the coil axis Ax in the circumferential direction of the first metal magnetic particles 31, but are not provided at the end in the direction perpendicular to the T-axis direction. Therefore, since the high magnetic permeability particles are not entirely surrounded by a magnetic gap, the decrease in inductance caused by the first magnetic gap elements 40a and 40b is also suppressed. Therefore, the magnetic base 10 according to the embodiment of the present invention can achieve both high magnetic permeability and high DC bias characteristics.
[0059] In one embodiment of the present invention, the magnetic substrate 10 may contain a binder that bonds the metal magnetic particles together. The binder is, for example, made of a thermosetting resin with excellent insulating properties. The resin material used as the binder has a smaller magnetic permeability than the first magnetic material. As the resin material for the binder, for example, epoxy resin, polyimide resin, polystyrene (PS) resin, high density polyethylene (HDPE) resin, polyoxymethylene (POM) resin, polycarbonate (PC) resin, polyvinylidene fluoride (PVDF) resin, phenolic resin, polytetrafluoroethylene (PTFE) resin, or polybenzoxazole (PBO) resin may be used.
[0060] Next, an example of a manufacturing method for the coil component 1 according to an embodiment of the present invention will be described with reference to Fig. 5. Fig. 5 illustrates an example of a manufacturing method for the coil component 1 according to an embodiment of the present invention. In the manufacturing method shown in Fig. 5, the coil component 1 is manufactured by a compression molding process.
[0061] First, in a preparation step, a mixed resin composition is produced by kneading a mixture of a plurality of first metal magnetic particles 31 and a plurality of second metal magnetic particles 32 with a resin and a diluting solvent. The resin may be an epoxy resin, a polyvinyl butyral (PVB) resin, or any other known resin.
[0062] Next, in step S11, a coil conductor 25 prepared in advance is placed in the cavity of a molding die, the molding die in which the coil conductor 25 is placed is filled with the mixed resin composition produced as described above, and molding pressure is applied to the mixed resin composition in the molding die with a punch to produce a molded body containing the coil conductor 25 therein. The coil conductor 25 is placed in the die cavity so that the coil axis Ax coincides or nearly coincides with the stroke direction (pressure direction) of the punch. If the angle between the coil axis and the stroke direction of the punch is within 30 degrees, it can be determined that the coil axis Ax coincides or nearly coincides with the pressure direction.
[0063] In the compression molding process of step S11, the mixed resin composition is compression molded at a molding pressure smaller than the elastic limit of the first metal magnetic particles 31 and larger than the elastic limit of the second metal magnetic particles 32 to produce a molded body. Due to this molding pressure, in the compression molding process of step S11, the first metal magnetic particles 31 are elastically deformed while the second metal magnetic particles 32 are plastically deformed. The specific molding pressure differs depending on the materials of the first metal magnetic particles 31 and the second metal magnetic particles 32, but is, for example, 5 to 15 ton / cm. 2 For example, when the first metal magnetic particles 31 are made of Fe-Si-Cr-B amorphous and the second metal magnetic particles 32 are made of carbonyl iron, the magnetic flux density can be set to 5 to 12 ton / cm. 2 Compression molding may be performed at a molding pressure in the range of 100 to 2000.
[0064] Since the molding pressure is greater than the elastic limit of the second metal magnetic particles 32, the second metal magnetic particles 32 are plastically deformed during the pressurization in the compression molding process, and stress acts from the plastically deformed second metal magnetic particles 32 to the first metal magnetic particles 31 in a direction perpendicular to the pressure direction (hereinafter referred to as the "pressure surface direction"). The pressure surface direction in the illustrated embodiment is a direction parallel to the WL surface. The first metal magnetic particles 31 are elastically deformed by the stress acting in the pressure surface direction from the second metal magnetic particles 32. The elastic deformation of the first metal magnetic particles 31 in the compression molding process will be described with reference to FIG. 6. FIG. 6(a) shows a schematic diagram of the cross-sectional shape of the first metal magnetic particles 31 before pressure, FIG. 6(b) shows a schematic diagram of the cross-sectional shape of the first metal magnetic particles 31 during pressure, and FIG. 6(c) shows a schematic diagram of the cross-sectional shape of the first metal magnetic particles 31 after unloading. As shown in FIG. 6(a), the cross-section of the first metal magnetic particles 31 is generally circular before pressure is applied. Although the cross-sectional shape of the first metal magnetic particle 31 is not limited to a circle, for the sake of simplicity, the shape of the first metal magnetic particle 31 is a circle in FIG. 6(a). When molding pressure is applied to the mixed resin composition in the mold cavity, as shown in FIG. 6(b), the first metal magnetic particle 31 is elastically compressed in the pressure surface direction due to the stress from the plastically deformed second metal magnetic particle 32 in the pressure surface direction, and assumes a shape that is more elongated in the pressure direction (T-axis direction) than before pressure is applied. Although a stress in the pressure direction also acts from the plastically deformed second metal magnetic particle 32 to the first metal magnetic particle 31, since the first metal magnetic particle 31 and the second metal magnetic particle 32 can move in the pressure direction in the mold cavity, the stress in the pressure direction acting on the first metal magnetic particle 31 promotes the movement of the first metal magnetic particle 31 in the pressure direction, but does not elastically compress the first metal magnetic particle 31 in the pressure direction. Although the second metal magnetic particles 32 are not shown in Fig. 6(b), as shown in Fig. 4, a large number of second metal magnetic particles 32 are present around the first metal magnetic particles 31. When the compact is removed from the die cavity after unloading, the compressive stress acting on the compact in the pressure surface direction is released, and the compact expands in the pressure surface direction. Therefore, the stress acting on the first metal magnetic particles 31 from the second metal magnetic particles 32 in the pressure surface direction is also released, and the first metal magnetic particles 31 return to their original shape as shown in Fig. 6(c).At this time, since the second metal magnetic particles 32 are plastically deformed, some springback occurs due to the unloading, but they do not return to their original shape. Therefore, in the compact after the unloading, voids 51a, 51b are generated at both ends of the first metal magnetic particles 31 in the pressure direction. The resin contained in the mixed resin composition may flow into these voids. In the completed magnetic base 10, these voids 51a, 51b and / or the resin that has flowed into these voids 51a, 51b become the first magnetic gap elements 40a, 40b.
[0065] After the molded body is obtained in the compression molding step, the manufacturing process proceeds to step S12. In step S12, the molded body obtained by the compression molding step is heat-treated, and the magnetic base 10 is produced from the molded body. Specifically, the resin in the mixed resin composition is cured by the heat treatment in step S12 to become a binder, and the binder binds the first metal magnetic particles 31 and the second metal magnetic particles 32. The heat treatment is performed at a temperature equal to or higher than the curing temperature of the resin in the mixed resin composition. The heat treatment in step S12 is performed, for example, at 150°C to 300°C for 30 minutes to 240 minutes.
[0066] The heat treatment in step S12 may oxidize the constituent elements of first metal magnetic particles 31, thereby forming an insulating film 41 containing an oxide of the constituent elements of first metal magnetic particles 31 on the surface of first metal magnetic particles 31.
[0067] Next, in step S13, a conductor paste is applied to the surface of the magnetic base 10 obtained in step S12 to form the external electrodes 21 and 22. The external electrode 21 is electrically connected to one end of the coil conductor 25 provided in the magnetic base 10, and the external electrode 22 is provided so as to be electrically connected to the other end of the coil conductor 25 provided in the magnetic base 10. The external electrodes 21 and 22 may include a plating layer. This plating layer may be two or more layers. The two plating layers may include a Ni plating layer and a Sn plating layer provided on the outside of the Ni plating layer. The coil conductor 25 may be arranged so that the end of the coil conductor 25 is exposed to the outside from the magnetic base 10, and the part of the coil conductor 25 exposed to the outside from the magnetic base 10 may be bent toward the mounting surface 10b to form the part of the coil conductor 25 exposed to the outside from the magnetic base 10 as the external electrode.
[0068] In this manner, the coil component 1 is manufactured. The manufactured coil component 1 may be mounted on the substrate 2 by a reflow process. In this case, the substrate 2 on which the coil component 1 is arranged passes through a reflow furnace heated to a peak temperature of, for example, 260° C. at high speed, and then the external electrodes 21, 22 are solder-joined to the land portions 3 of the mounting substrate 2a, thereby mounting the coil component 1 on the mounting substrate 2a and obtaining the circuit substrate 2.
[0069] As described above, the insulating film 41 may be a coating film made of an insulating material. When the insulating film 41 is a coating film, the first metal magnetic particles 31 having an insulating film formed on their surfaces are prepared in the preparation step. The coating film may also be provided on the surfaces of the second metal magnetic particles 32.
[0070] With reference to FIG. 7, the magnetic gap portion 40 in another embodiment of the present invention will be described. FIG. 7 is a diagram showing the magnetic gap portion 40 in another embodiment of the present invention by enlarging the region B of the magnetic base in FIG. 3. In the embodiment shown in FIG. 7, the magnetic gap portion 40 differs from the embodiment shown in FIG. 3 in that it includes an insulating film 141 instead of the insulating film 41. The insulating film 141 is configured so that its thicknesses T121a and 121b in the T-axis direction are thicker than its thicknesses T122a and T122b in the L-axis direction perpendicular to the T-axis direction. The insulating film 141 has thicknesses T121a and 121b in the T-axis direction of, for example, 100 to 3000 nm, and its thicknesses T122a and T122b in the L-axis direction of, for example, less than 100 nm. The thickness of the insulating film 141 in the W-axis direction is not shown, but is the same or approximately the same as the thickness in the L-axis direction, specifically, smaller than the thicknesses T121a and 121b in the T-axis direction. Thicknesses T121a, 121b of insulating film 141 in the T-axis direction refer to the length of a portion of a straight line obtained by extending line segment L1, the longest of the line segments that are parallel to the T-axis and overlap with the cross section of first metal magnetic particle 31, to the positive side in the T-axis direction, where this straight line intersects with insulating film 141. Thickness dimensions T122a, T122b of insulating film 141 in the L-axis direction are defined and measured in the same way as thickness dimensions T121a, T121b in the T-axis direction.
[0071] The insulating film 141 is formed by adjusting the heating conditions in the heat treatment in step S12 described above and the composition of the first metal magnetic particles 31. Specifically, by performing the heat treatment in step S12 under heating conditions that facilitate the formation of an oxide film on the surface of the first metal magnetic particles 31, the voids 51a, 51b formed in step S11 are filled with an oxide film of the constituent elements of the first metal magnetic particles 31, thereby forming the insulating film 141.
[0072] The magnetic gap portion 40 shown in Fig. 7 does not include the first magnetic gap elements 40a, 40b. The magnetic gap portion 40 shown in Fig. 7 may include the first magnetic gap elements 40a, 40b. For example, when a part of the voids 51a, 51b formed in step S11 is filled with an oxide film of the constituent elements of the first metal magnetic particles 31 and the remaining part remains as a void, or when resin flows into the void, the region of the voids 51a, 51b that is not filled with the oxide film becomes the first magnetic gap elements 40a, 40b.
[0073] Next, a coil component 1 according to another embodiment of the present invention will be described with reference to Fig. 8. The coil component 1 shown in Fig. 8 is a laminated coil.
[0074] The magnetic base 10 can be produced by stacking a plurality of magnetic sheets 11-17 in the T-axis direction and thermocompressing the stacked magnetic sheets. As described above, the magnetic base 10 includes a plurality of first metal magnetic particles 31 and a plurality of second metal magnetic particles 32, and has a magnetic gap portion 40 made of a low magnetic permeability material having a relative magnetic permeability lower than that of the material of the first metal magnetic particles 31. As described above, the magnetic gap portion 40 is configured such that the thickness dimension in the T-axis direction is larger than the thickness dimension in the directions perpendicular to the T-axis direction (the L-axis direction and the W-axis direction).
[0075] The coil conductor 25 extends around the coil axis Ax extending in the T-axis direction. As shown in the figure, the coil conductor 25 has conductor patterns C1 to C5 and via conductors V1 to V4 that connect adjacent ones of the conductor patterns C1 to C5. The via conductors V1 to V4 can be produced by filling through holes extending in the T-axis direction formed in the magnetic sheets 12 to 15 with conductive paste. The conductor patterns C1 to C5 are formed, for example, by printing a conductive paste made of a metal or alloy with excellent conductivity on the magnetic sheets by, for example, a screen printing method. The conductive paste may be made of Ag, Pd, Cu, Al, or an alloy thereof. Each of the conductor patterns C1 to C5 is electrically connected to the adjacent conductor patterns via the via conductors V1 to V4. The conductor patterns C1 to C5 and the via conductors V1 to V4 connected in this way form the coil conductor 25 that extends in a spiral shape around the coil axis Ax.
[0076] Next, an example of a method for manufacturing the coil component 1 shown in FIG. 8 will be described. The coil component 1 shown in FIG. 8 can be manufactured by a lamination process. First, a plurality of magnetic sheets 11-17 made of a magnetic material are created. Each of these magnetic sheets 11-17 is produced by kneading a mixture of a plurality of first metal magnetic particles 31 and a plurality of second metal magnetic particles 32 with a binder resin (e.g., polyvinyl butyral (PVB) resin) and a dilution solvent (e.g., toluene) to generate a mixed resin composition, applying the generated mixed resin composition in a sheet shape onto a substrate such as a PET film by, for example, a doctor blade method, and drying the applied mixed resin composition to volatilize the dilution solvent.
[0077] Next, through holes are formed in the magnetic sheets 12-15 at predetermined positions thereof, penetrating each of them in the T-axis direction. Next, a conductive paste is printed on the upper surface of each of the magnetic sheets 12-16 by screen printing, thereby forming unsintered conductor patterns on the magnetic sheets 12-16, and filling each of the through holes formed in the magnetic sheets 12-15 with the conductive paste. The unsintered conductor patterns formed on the magnetic sheets 12-16 are precursors of the conductor patterns C1-C5, respectively, and the conductive paste filled in the through holes of the magnetic sheets 12-15 are precursors of the via conductors V1-V4, respectively.
[0078] Next, after the conductive paste is dried, the magnetic sheets 11-17 are laminated. The magnetic sheets 11-17 are laminated such that the precursors of the conductor patterns C1-C5 formed on each magnetic sheet are electrically connected to adjacent ones via the precursors of the via conductors V1-V4. Next, the magnetic sheets laminated as described above are thermocompression-bonded by a press machine to produce a sheet laminate. In this thermocompression-bonding process, the sheet laminate is pressed along the lamination direction of the magnetic sheets 11-17 with a pressure smaller than the elastic limit of the first metal magnetic particles 31 and larger than the elastic limit of the second metal magnetic particles 32. Specifically, the sheet laminate is placed in the cavity of a molding die, and a molding pressure is applied to the sheet laminate in the die cavity with a punch, thereby producing a molded body containing the precursors of the conductor patterns C1-C5 inside. The sheet laminate is placed in the die cavity such that the coil axis Ax coincides or nearly coincides with the stroke direction (pressure direction) of the punch. If the angle between the coil axis Ax and the stroke direction of the punch is within 30 degrees, it can be determined that the coil axis Ax and the pressure direction coincide or nearly coincide.
[0079] In the compression molding process to form the sheet laminate, the sheet laminate is compression molded at a molding pressure smaller than the elastic limit of the first metal magnetic particles 31 and larger than the elastic limit of the second metal magnetic particles 32 to produce a molded body. This molding pressure causes the first metal magnetic particles 31 to elastically deform while the second metal magnetic particles 32 to plastically deform. The specific molding pressure differs depending on the materials of the first metal magnetic particles 31 and the second metal magnetic particles 32, but is, for example, 5 to 15 ton / cm. 2 For example, when the first metal magnetic particles 31 are made of Fe-Si-Cr-B amorphous and the second metal magnetic particles 32 are made of carbonyl iron, the magnetic flux density can be set to 5 to 12 ton / cm. 2 Compression molding may be performed at a molding pressure in the range of 100 to 2000.
[0080] Since the molding pressure in the compression molding process on the sheet laminate is greater than the elastic limit of the second metal magnetic particles 32, the second metal magnetic particles 32 are plastically deformed during the pressure application in the compression molding process, and stress acts from the plastically deformed second metal magnetic particles 32 to the first metal magnetic particles 31 in a direction perpendicular to the pressure application direction (hereinafter referred to as the "pressure surface direction"). In the illustrated embodiment, the pressure surface direction is a direction parallel to the WL plane. The first metal magnetic particles 31 are elastically deformed by the stress acting in the pressure surface direction from the second metal magnetic particles 32. The elastic deformation of the first metal magnetic particles 31 in the compression molding process and the resulting formation of the first magnetic gap elements 40a, 40b are the same as in embodiment 1, so a description thereof will be omitted.
[0081] Next, the thermocompression-bonded sheet laminate is diced into pieces of a desired size using a cutting machine such as a dicing machine or a laser processing machine to obtain a chip laminate. Next, the chip laminate is degreased, and the degreased chip laminate is heat-treated. This heat treatment oxidizes the surfaces of the first metal magnetic particles 31 and the second metal magnetic particles 32, and the first metal magnetic particles 31 and the second metal magnetic particles 32 are covered with an oxide film. The oxide film bonds adjacent metal magnetic particles to each other. The heat treatment is performed at a temperature of, for example, 350°C to 900°C, for example, for 30 minutes to 360 minutes. The degreasing may be performed separately from the heat treatment for oxidizing the first metal magnetic particles 31 and the second metal magnetic particles 32. In the degreasing treatment performed separately from the heat treatment for the first metal magnetic particles 31 and the second metal magnetic particles 32, the chip laminate is heated at 200°C to 400°C for, for example, 20 minutes to 120 minutes. The prominent first magnetic gap elements 40a, 40b generated during molding remain as voids even after heat treatment, becoming the first magnetic gap elements 40a, 40b. The voids of the first magnetic gap elements 40a, 40b can be impregnated with resin or the like as necessary.
[0082] Next, the ends of this chip stack are polished, such as by barrel polishing, if necessary. Next, external electrodes are formed by applying a conductive paste to both ends of this chip stack. Through the above steps, coil component 1 is obtained by the stacking process.
[0083] Next, a coil component 1 according to another embodiment of the present invention will be described with reference to FIG. 9. The coil component 1 according to one embodiment of the present invention is a wire-wound inductor. As shown in the figure, the coil component 1 in the embodiment shown in FIG. 9 includes a drum-shaped magnetic base 10, a coil conductor 25, a first external electrode 21, and a second external electrode 22. The magnetic base 10 has a winding core 111, a rectangular parallelepiped flange 112a provided at one end of the winding core 111, and a rectangular parallelepiped flange 112b provided at the other end of the winding core 111. The winding core 111 extends along the coil axis Ax. The coil conductor 25 is wound around the winding core 111. That is, the coil conductor 25 extends in a spiral shape around the coil axis Ax. The coil conductor 25 has a conductive wire made of a metal material with excellent conductivity and an insulating coating that covers the periphery of the conductive wire. The first external electrode 21 is provided along the lower surface of the flange 112a, and the second external electrode 22 is provided along the lower surface of the flange 112b.
[0084] As described above, the magnetic base 10 includes a plurality of first metal magnetic particles 31 and a plurality of second metal magnetic particles 32, and has a magnetic gap portion 40 made of a low-permeability material having a relative permeability lower than that of the material of the first metal magnetic particles 31. As described above, this magnetic gap portion 40 is configured so that the thickness dimension in the T-axis direction is larger than the thickness dimension in the directions perpendicular to the T-axis direction (the L-axis direction and the W-axis direction).
[0085] Next, an example of a manufacturing method of the wound coil component 1 shown in FIG. 9 will be described. First, a mixed resin composition is compression molded to produce a magnetic base 10. In this compression molding process, a mixed particle of a plurality of first metal magnetic particles 31 and a plurality of second metal magnetic particles 32 is kneaded with a resin and a dilution solvent to obtain a mixed resin composition. Metal magnetic particles are dispersed in this mixed resin composition. This mixed resin composition is placed in a molding die, and the mixed resin composition in the molding die is heated while being compressed at 5 to 15 ton / cm. 2A compact is produced by applying a molding pressure of 100 to 150 mm. The direction of the molding pressure is parallel to the axis of the winding core 111. The axis of the winding core 111 becomes the coil axis Ax when completed.
[0086] Next, a heat treatment step is performed in which the molded body obtained by the compression molding step is heat-treated. The magnetic base 10 is formed from the molded body by this heat treatment step. Specifically, in the heat treatment step, the resin in the mixed resin composition is cured to become a binder, and the binder binds the first metal magnetic particles 31 and the second metal magnetic particles 32. The heat treatment is performed at a temperature equal to or higher than the curing temperature of the resin in the mixed resin composition, for example, at 150°C to 300°C, for 30 minutes to 240 minutes.
[0087] Next, a winding step is performed to provide a coil conductor 25 on the magnetic base 10 obtained by the above heat treatment step. In the winding step, the coil conductor 25 is wound around the winding core 111 of the magnetic base 10. Next, one end of the coil conductor 25 is connected to the first external electrode 21, and the other end is connected to the second external electrode 22. In this manner, a wire-wound coil component 1 is obtained.
[0088] As described above, the magnetic base 10 includes a plurality of first metal magnetic particles 31 and a plurality of second metal magnetic particles 32, and has a prominent first magnetic gap element 40a and / or a first magnetic gap element 40a at at least one end of the first metal magnetic particle 31 in a direction parallel to the coil axis Ax. EXAMPLES
[0089] Example 1 First, Fe-Si-B amorphous particles with an average particle size of 20 μm were prepared as the first metal magnetic particles 31, and carbonyl iron particles with an average particle size of 5 μm were prepared as the second metal magnetic particles 32. These two types of metal magnetic powders were mixed at a volume ratio of 30:70 to obtain mixed particles. The elastic limit of carbonyl iron is smaller than that of Fe-Si-B amorphous. The relative magnetic permeability of carbonyl iron is also smaller than that of Fe-Si-B amorphous. Next, 3 wt% of epoxy resin was kneaded with 100 wt% of the mixed particles to generate a mixed resin composition. An enamel-coated copper wire with a diameter of 2 mm was wound around the coil axis Ax for 4.5 turns to produce a coil conductor 25. The enamel coating was removed from each of the portions 1.5 mm from both ends of the coil conductor 25, and a solder layer was formed on the portions where the enamel coating was removed. This coil conductor 25 was placed in the die cavity of a molding die so that the coil axis Ax was approximately aligned with the pressure direction. Next, the die cavity was filled with the above mixed resin composition, and a pressure of 12 ton / cm 2 A molding pressure of 12 ton / cm was applied to produce a compact containing the coil conductor 25 therein. The molding pressure was applied in a direction parallel to the coil axis Ax of the coil conductor 25. 2 The pressure is greater than the elastic limit of carbonyl iron and less than the elastic limit of Fe-Si-B amorphous.
[0090] Next, after the molding pressure was released, the molded body was removed from the mold cavity, and the molded body removed from the mold cavity was heat-treated at 200°C for 60 minutes to harden the epoxy resin in the mixed resin composition, thereby forming the magnetic base 10 from the molded body. After the heat treatment, the end of the coil conductor 25 was bent to face the mounting surface 10b of the magnetic base 10. The coil component produced in the above manner was designated as Sample 1.
[0091] The coil component (sample 1) produced as described above was cut along the coil axis Ax to expose the cross section, and the cross section was photographed at a magnification of 1000 times to obtain an SEM image. EDS analysis was performed on this SEM image to analyze the composition of each particle, and 20 particles with a lower molar ratio of iron were selected as the observation target particles. For 16 of these observation target particles, voids covering at least one end in the direction along the coil axis Ax were observed. In addition, the average value of the dimension in the direction along the coil axis Ax of the voids covering at least one end in the direction along the coil axis Ax of the observation target particles was 630 nm. The dimension in the direction along the coil axis Ax of the voids covering at least one end of the coil axis Ax of the observation target particles was measured by the same method as the measurement method of the dimensions T21a and 21b described above. No insulating film was observed on the surface of the observation target particle. Therefore, the voids covering the end of the observation target particle in the direction along the coil axis Ax correspond to the magnetic gap portion 40.
[0092] Example 2 Next, Fe-Si alloy particles (Fe: 93.5 wt%, Si: 6.5 wt%) with an average particle size of 10 μm were prepared as the first metal magnetic particles 31, and Fe-Si alloy particles (Fe: 97 wt%, Si: 3 wt%) with an average particle size of 10 μm were prepared as the second metal magnetic particles 32, and these two types of metal magnetic powders were mixed to a volume ratio of 30:70 to obtain mixed particles. Since the content ratio of Si in the second metal magnetic particles 32 is smaller than the content ratio of Si in the first metal magnetic particles 31, the elastic limit of the second metal magnetic particles 32 is smaller than the elastic limit of the first metal magnetic particles 31, and the relative magnetic permeability of the second metal magnetic particles 32 is smaller than the relative magnetic permeability of the first metal magnetic particles 31. Using this mixed particle, a coil component was produced in the same manner as in Example 1. The coil component produced in the above manner is designated as Sample 2. However, the compaction pressure used to prepare the compact was 6 ton / cm, which is greater than the elastic limit of Fe-Si alloy particles with 97 wt% Fe and 3 wt% Si, but smaller than the elastic limit of Fe-Si alloy particles with 93.5 wt% Fe and 6.5 wt% Si. 2 It was decided.
[0093] The coil component (sample 2) produced as described above was cut along the coil axis Ax to expose the cross section, and the cross section was photographed at a magnification of 1000 times to obtain an SEM image. EDS analysis was performed on this SEM image to analyze the composition of each particle, and 20 particles with a lower molar ratio of iron were selected as the observation target particles. For 14 of these observation target particles, voids covering at least one end in the direction along the coil axis Ax were observed. In addition, the average value of the dimension in the direction along the coil axis Ax of the voids covering at least one end in the direction along the coil axis Ax of the observation target particles was 120 nm. The dimension in the direction along the coil axis Ax of the voids covering at least one end of the coil axis Ax of the observation target particles was measured by the same method as the measurement method of the dimensions T21a and 21b described above. No insulating film was observed on the surface of the observation target particle. Therefore, the voids covering the end of the observation target particle in the direction along the coil axis Ax correspond to the magnetic gap portion 40.
[0094] Example 3 Next, Fe-Si-Cr alloy particles (Fe: 92 wt%, Si: 6.5 wt%, Cr: 1.5 wt%) with an average particle size of 4 μm were prepared as the first metal magnetic particles 31, and Fe-Si-Cr alloy particles (Fe: 95 wt%, Si: 3 wt%, Cr: 2 wt%) with an average particle size of 3 μm were prepared as the second metal magnetic particles 32, and these two types of metal magnetic powders were mixed to a volume ratio of 30:70 to obtain mixed particles. Since the content ratio of Si in the second metal magnetic particles 32 is smaller than the content ratio of Si in the first metal magnetic particles 31, the elastic limit of the second metal magnetic particles 32 is smaller than the elastic limit of the first metal magnetic particles 31, and the relative magnetic permeability of the second metal magnetic particles 32 is smaller than the relative magnetic permeability of the first metal magnetic particles 31. Using this mixed particle, a coil component was manufactured by a lamination process. Specifically, the mixed particles were kneaded with polyvinyl butyral resin and toluene to produce a mixed resin composition, and the mixed resin composition was applied to a PET film in the form of a sheet by a doctor blade method. The mixed resin composition applied to the film was dried to volatilize the dilution solvent, thereby producing a plurality of magnetic sheets. Next, through holes for embedding via conductors V1 to V4 were formed in four of the magnetic sheets. Next, a conductive paste was printed on the upper surface of each of the four magnetic sheets with the through holes formed therein and one magnetic sheet without the through holes formed therein as described above, and the conductive paste was filled in the through holes to form precursors of the conductor patterns C1 to C5 and the vias V1 to V4 shown in FIG. 8. After the conductive paste was dried, the five magnetic sheets with the precursors of the conductor patterns formed thereon and the two magnetic sheets without the conductor patterns formed thereon were stacked so that the two magnetic sheets without the conductor patterns formed thereon were located at the upper and lower ends, respectively, and a pressure of 6 ton / cm was applied to the stacked magnetic sheets along the stacking direction. 2 The magnetic sheets were thermocompression-bonded by applying a pressure of 6 ton / cm to produce a sheet laminate. 2The pressure is greater than the elastic limit of Fe-Si-Cr alloy particles (second metal magnetic particles 32) containing 95 wt% Fe, 3% Si, and 2 wt% Cr, and is less than the elastic limit of Fe-Si-Cr alloy particles (first metal magnetic particles 31) containing 92 wt% Fe, 6.5% Si, and 1.5 wt% Cr.
[0095] Next, the thermocompression-bonded sheet laminate was cut into individual pieces to produce a chip laminate. Next, this chip laminate was heat-treated at 750°C for 60 minutes in an oxygen-containing atmosphere to thermally decompose the polyvinyl butyral resin and form an oxide film on the surface of the metal magnetic particles, thereby producing the magnetic base 10 and the coil conductor 25. Next, a conductive paste produced by kneading silver particles with ethyl cellulose and butyl carbitol was applied to the surface of the magnetic base 10, and the applied conductive paste was baked to produce a base electrode layer. Next, a nickel-tin plating layer was formed on the surface of this base electrode layer. In this manner, an external electrode having a base electrode layer and a plating layer was formed on the surface of the magnetic base 10. The coil component produced in this manner is designated as sample 3.
[0096] The coil component (sample 3) produced as described above was cut along the coil axis Ax to expose the cross section, and the cross section was photographed at a magnification of 1000 times to obtain an SEM image. EDS analysis was performed on this SEM image to analyze the composition of each particle, and 20 particles with a lower molar ratio of iron were selected as the observation target particles. Voids covering at least one end in the direction along the coil axis Ax were observed for 15 of the observation target particles. In addition, the average value of the dimension in the direction along the coil axis Ax of the voids covering at least one end in the direction along the coil axis Ax of the observation target particles was 65 nm. The dimension in the direction along the coil axis Ax of the voids covering at least one end of the coil axis Ax of the observation target particles was measured by the same method as the measurement method of the dimensions T21a and 21b described above. No insulating film was observed on the surface of the observation target particle. Therefore, the voids covering the end in the direction along the coil axis Ax of the observation target particle correspond to the magnetic gap portion 40.
[0097] Comparative Example 1 In the manufacturing method of sample 2, the molding pressure was set to 10 ton / cm 2 The coil parts were manufactured under the same manufacturing conditions as Sample 2, except for the above. 2 The pressure is greater than the elastic limit of the Fe-Si alloy particles (first metal magnetic particles 31) with Fe: 93.5 wt % and Si: 6.5%. The coil component (sample 4) produced as described above was cut along the coil axis Ax to expose the cross section, and the cross section was photographed at a magnification of 1000 times to obtain an SEM image. EDS analysis was performed on this SEM image to analyze the composition of each particle, and 20 particles with a lower molar ratio of iron were selected as observation target particles. In none of the observation target particles were any voids covering the ends in the T-axis direction or other regions corresponding to the first magnetic gap elements 40a and 40b. The reason why no magnetic gap portion was formed at the ends in the T-axis direction of the first metal magnetic particles 31 is thought to be because a molding pressure greater than the elastic limit of the first metal magnetic particles 31 was used in the manufacturing process of sample 4, and the first metal magnetic particles 31 were also plastically deformed and could not return to their shape before pressure was applied after the load was removed.
[0098] Comparative Example 2 In the manufacturing method of sample 2, the molding pressure was set to 1 ton / cm 2 The coil parts were manufactured under the same manufacturing conditions as Sample 2, except for the above. 2The pressure is smaller than the elastic limit of the Fe-Si alloy particles (second metal magnetic particles 32) of Fe: 97 wt % and Si: 3%. The coil component (sample 5) manufactured as described above was cut along the coil axis Ax to expose the cross section, and the cross section was photographed at a magnification of 1000 times to obtain an SEM image. EDS analysis was performed on this SEM image to analyze the composition of each particle, and 20 particles with a lower molar ratio of iron were selected as observation target particles. Each of these observation target particles had a large distance from the adjacent particles and was surrounded by resin. Thus, in sample 5, no voids covering the ends in the T-axis direction or other areas corresponding to the first magnetic gap elements 40a, 40b were observed in any of the observation target particles. The reason why the first magnetic gap elements 40a, 40b, which cover only a portion of the surface of the first metal magnetic particle 31 but not the entire surface, were not formed at the ends in the T-axis direction of the Fe-Si alloy particles (first metal magnetic particles 31) made of 93.5 wt% Fe and 6.5% Si, is thought to be because a molding pressure lower than the elastic limit of the second metal magnetic particles 32 was used in the manufacturing process of sample 5, and therefore the first metal magnetic particles 31 and the second metal magnetic particles 32 were not densely packed.
[0099] Comparative Example 3 In the manufacturing method of Sample 1, the direction of the molding pressure was changed to a direction perpendicular to the coil axis Ax, and otherwise a coil component was manufactured under the same conditions as the manufacturing method of Sample 1. The coil component (Sample 6) manufactured in this way was cut along the coil axis Ax to expose the cross section, and the cross section was photographed at a magnification of 1000 times to obtain an SEM image. EDS analysis was performed on this SEM image to analyze the composition of each particle, and 20 particles with a lower molar ratio of iron were selected as observation target particles. For 10 of these observation target particles, voids covering at least one direction perpendicular to the coil axis Ax were observed. However, the observed voids did not cover the ends of the first metal magnetic particles 31 in the direction along the coil axis Ax, and therefore were not voids corresponding to the first magnetic gap elements 40a, 40b. For this reason, as described below, the DC superposition characteristics of Sample 6 were low.
[0100] An impedance analyzer was used to measure the inductance and the DC bias rated current for each of Samples 1 to 6. The measurement results are shown in Table 1. [Table 1]
[0101] As shown in Table 1, for Samples 1 to 3 in which a magnetic gap portion is provided at the end of the first metal magnetic particle 31 in the direction along the coil axis, the inductance was 1.0 μH and the DC superimposed rated current was in the range of 8.0 to 8.5 A. The measurement results of Sample 2 and Sample 4 will be compared and considered. The manufacturing methods of Sample 2 and Sample 4 are the same except for the molding pressure, but the DC superimposed rated current of Sample 2, in which a molding pressure smaller than the elastic limit of the first metal magnetic particle 31 and larger than the elastic limit of the second metal magnetic particle 32 was applied, was 8.2 A, which is a significant improvement from 5.5 A of Sample 4, in which a molding pressure larger than the elastic limit of the first metal magnetic particle 31 was applied. This improvement in the DC superimposition characteristics is believed to be due to the contribution of the gaps (first magnetic gap elements 40a, 40b) formed in the magnetic base 10 of Sample 2 so as to cover the end of the first metal magnetic particle 31 in the T-axis direction. On the other hand, the inductance of Sample 2 was 1.0 μH, which was only slightly lower than the 1.2 μH of Sample 4. Next, the measurement results of Sample 2 and Sample 5 are compared and considered. The manufacturing methods of Sample 2 and Sample 5 are the same except for the molding pressure, but the inductance of Sample 5, which was produced by applying a molding pressure smaller than the elastic limit of the second metal magnetic particles 32, is 0.5 μH, which is significantly inferior to the 1.0 μH of Sample 2. From the above results, it was found that by applying a molding pressure smaller than the elastic limit of the first metal magnetic particles 31 and larger than the elastic limit of the second metal magnetic particles 32 to provide a magnetic gap portion at the end of the first metal magnetic particles 31 in the direction along the coil axis, it is possible to achieve both high magnetic permeability (inductance) and high DC superposition characteristics (DC superposition rated current).
[0102] Comparing the DC bias rated current of Sample 1 and Sample 6, which differ only in the pressure direction relative to the coil axis, Sample 1 achieves a superior DC bias rated current. From this comparison, it was found that the degree of improvement in the DC bias characteristics is increased by providing gaps equivalent to first magnetic gap elements 40a, 40b at the ends of first metal magnetic particles 31 in the direction along the coil axis.
[0103] As described above, according to at least one embodiment of the present invention, the magnetic gap portion 40 is provided to cover the surface of the first metal magnetic particle 31 where magnetic saturation is likely to occur, and the thickness dimension of this magnetic gap portion 40 in the direction along the coil axis Ax is greater than the thickness dimension in the direction perpendicular to the coil axis Ax. This magnetic gap portion 40 can suppress the magnetic flux flowing in the magnetic base 10 along the coil axis Ax from concentrating on the magnetic path passing through the first metal magnetic particle 31, thereby obtaining high DC superposition characteristics. In addition, by making the thickness of the magnetic gap portion 40 in the direction perpendicular to the coil axis Ax thinner than the thickness in the direction along the coil axis Ax, it is possible to suppress the decrease in magnetic permeability, and therefore it is possible to achieve both high magnetic permeability and high DC superposition characteristics.
[0104] The dimensions, materials, and arrangements of each component described in the various embodiments above are not limited to those explicitly described in each embodiment, and each component can be modified to have any dimensions, materials, and arrangements that can be included in the scope of the present invention. For example, the magnetic base 10 may be configured and arranged to cover the coil conductor 25 as shown in Figures 1 and 2, or may be configured and arranged so that the coil conductor 25 is wound around its outer surface as shown in Figure 9.
[0105] Components not explicitly described in this specification may be added to each of the above-described embodiments, and some of the components described in each embodiment may be omitted.
[0106] The designations "first," "second," "third," and the like in this specification are given to identify components, and do not necessarily limit the number, order, or content. Furthermore, numbers for identifying components are used in different contexts, and a number used in one context does not necessarily indicate the same configuration in another context. Furthermore, a component identified by a certain number does not prevent the component from also having the function of a component identified by another number. [Explanation of symbols]
[0107] 1 Coil parts 10 Magnetic substrate 21, 22 External electrode 25 Coil conductor 31 First metal magnetic particles 32 Second metal magnetic particles 40 Magnetic gap section 40a, 40b First magnetic gap element 41, 141 Insulating film (second magnetic gap element) Ax Coil axis
Claims
1. a coil conductor extending around a coil axis; a magnetic base including a coil axis, the magnetic base including: first metal magnetic particles having a first elastic limit and a first relative magnetic permeability; second metal magnetic particles having a second elastic limit smaller than the first elastic limit and a second relative magnetic permeability lower than the first relative magnetic permeability; and a magnetic gap portion covering a surface of the first metal magnetic particles and configured such that a first thickness in a first direction along the coil axis is greater than a second thickness in a second direction perpendicular to the first direction; A coil component comprising:
2. the magnetic gap portion is composed of at least one of an air gap and a resin, and has a first magnetic gap element covering one end of the first metal magnetic particle in the first direction; The coil component according to claim 1 .
3. the first magnetic gap element extends in a circumferential direction of the first metal magnetic particle over a length of 1 / 16 or more and less than 1 / 2 of a circumferential length of the first metal magnetic particle when observed in a cross section of the magnetic base cut along a plane passing through the coil axis; The coil component according to claim 2 .
4. the magnetic gap portion has a second magnetic gap element including an oxide of an element contained in the first metal magnetic particle; The coil component according to claim 1 or 2.
5. The thickness of the second magnetic gap element in the first direction is greater than the thickness of the second magnetic gap element in the second direction. The coil component according to claim 4 .
6. When observed in a cross section of the magnetic base cut along a plane passing through the coil axis, the dimension of the magnetic gap portion in the first direction is 0.5% to 4.0% of the dimension of the first metal magnetic particle in the first direction. The coil component according to claim 1 .
7. the first metal magnetic particles and the second metal magnetic particles are both made of an Fe—Si alloy, The content ratio of Si in the first metal magnetic particles is higher than the content ratio of Si in the second metal magnetic particles. The coil component according to claim 1 .
8. The Fe content of the first metal magnetic particles is lower than the Fe content of the second metal magnetic particles. The coil component according to claim 7.
9. In the magnetic base, a volume ratio of the first metal magnetic particles to a total volume of the first metal magnetic particles and the second metal magnetic particles is in a range of 10 to 65 vol %. The coil component according to claim 1 .
10. the magnetic base is formed by pressing an element including the first metal magnetic particles and the second metal magnetic particles in the first direction. The coil component according to claim 1 .
11. the magnetic gap portion is composed of at least one of an air gap and a resin, and has another first magnetic gap element covering the other end of the first metal magnetic particle in the first direction; The coil component according to claim 1 .
12. A circuit board comprising the coil component according to claim 1 .
13. An electronic device comprising the circuit board according to claim 12.
14. a step of filling a magnetic material including first metal magnetic particles having a first relative magnetic permeability and second metal magnetic particles having a second relative magnetic permeability lower than the first relative magnetic permeability into a die cavity in which a coil conductor extending around a coil axis is disposed, and pressurizing the magnetic material in a direction along the coil axis at a molding pressure smaller than the elastic limit of the first metal magnetic particles and larger than the elastic limit of the second metal magnetic particles to form a molded body; a step of heat-treating the compact after removing the molding pressure to form a magnetic substrate; A method for manufacturing a coil component comprising the steps of:
15. A step of producing a plurality of magnetic sheets from a mixed magnetic material including first metal magnetic particles having a first relative magnetic permeability and second metal magnetic particles having a second relative magnetic permeability lower than the first relative magnetic permeability; forming a conductive pattern on a surface of each of the plurality of magnetic sheets; a step of stacking the plurality of magnetic sheets on which the conductive patterns are formed in a stacking direction to electrically connect the conductive patterns to each other, thereby forming a laminate having a coil axis along the stacking direction; forming a compact by pressing the stack in the stacking direction with a pressure smaller than the elastic limit of the first metal magnetic particles and larger than the elastic limit of the second metal magnetic particles; a step of heat-treating the compact after removing the molding pressure to form a magnetic substrate; A method for manufacturing a coil component comprising the steps of:
16. a step of applying a molding pressure in one axial direction to a mixed magnetic material including first metal magnetic particles having a first relative magnetic permeability and second metal magnetic particles having a second relative magnetic permeability lower than the first relative magnetic permeability, the molding pressure being smaller than the elastic limit of the first metal magnetic particles and larger than the elastic limit of the second metal magnetic particles, to form a compact; heat-treating the compact to form a magnetic substrate; providing a coil conductor on the magnetic base so as to extend around the one axial direction; A method for manufacturing a coil component comprising the steps of:
Citation Information
Patent Citations
Dust core of fe-si-al alloy
JP1988271905A
Coil component, circuit board, and electronic apparatus
JP2021121006A
Coil component and electronic apparatus
JP2021163853A
